I'm dancing as fast as I can - Gordon, Barbara 1935- (Bantam Books, 1980)
Here is an incredible heroine who was at the top of her field, a TV producer with a marvelous lover, plenty of money, good health and a lot of talent and luck. Then, suddenly, Barbara Gordon's life fell to pieces.